2018
DOI: 10.1002/bsl.2379
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment communication difficulties: An empirical examination of the effects of categorical versus probabilistic risk communication in sexually violent predator decisions

Abstract: Expert testimony concerning risk and its communication to the trier of fact has important implications for some of the most significant legal decisions. In a simulated sexual violent predator hearing, we examined how mock jurors interpret and use recidivism risk expert testimony communicated either categorically, using verbal labels, or probabilistically, using numeric values. Based upon the STATIC‐99R, we compared mock jurors' decision‐making and verdicts when we manipulated the style of risk communication ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…Notwithstanding these aims, there are fundamental barriers in the literature impeding upon clear risk communication. Research has consistently shown both judges and laypeople prefer categorical descriptions of risk despite the fact that categorical communication can lead to an overestimation of risk, leading to higher conviction rates, or harsher sentences (Krauss et al, 2018;Scurich, 2018). Risk communicated in a frequency format (e.g., 1 in 10) has been shown to lead to lower likelihoods of commitment decisions than risk communicated in a probability format (e.g., 10% chance), though both are numerically equal (Slovic et al, 2000).…”
Section: Table Of Contentsmentioning
confidence: 99%
See 4 more Smart Citations
“…Notwithstanding these aims, there are fundamental barriers in the literature impeding upon clear risk communication. Research has consistently shown both judges and laypeople prefer categorical descriptions of risk despite the fact that categorical communication can lead to an overestimation of risk, leading to higher conviction rates, or harsher sentences (Krauss et al, 2018;Scurich, 2018). Risk communicated in a frequency format (e.g., 1 in 10) has been shown to lead to lower likelihoods of commitment decisions than risk communicated in a probability format (e.g., 10% chance), though both are numerically equal (Slovic et al, 2000).…”
Section: Table Of Contentsmentioning
confidence: 99%
“…Research has also examined the effect of risk communication on laypeople. In a mock Sexually Violent Predator (SVP) commitment hearing, jurors presented with a categorical estimate were more likely to commit 'high risk' individuals than individuals given a probabilistic estimate (e.g., 13% likely to reoffend in 10 years) that equated to a 'high risk' decision on the Static-99R (Krauss et al, 2018). Commitment decisions were found to increase as categorical risk level increased, while these results were not replicated when jurors were presented with probabilistic estimates.…”
Section: Categorical Risk Estimatesmentioning
confidence: 99%
See 3 more Smart Citations